Consolidation of Financial Reporting: Realities and Prospects (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article the economic bases of business associations and their aim are investigated. The regulation of the procedure for the creation and operation of associations of companies is considered at the legislative level. After all, one of the most promising directions of business development for today is the creation of companies that are connected by an economic component, but at the same time by independent legal entities – concerns or holding companies. The article outlines the features of the merger of enterprises as a legal entity. The research of the quantity of institutions of Ukraine with the potential control relations was conducted (data of the State Statistics Committee of Ukraine). Normative legal adjusting and basic changes in relation to the consolidated financial reporting are reviewed. The composition and requirements for consolidated financial reporting of enterprises of Ukraine concerning the «modernized» law on accounting records are researched.The results of the study showed that the formation and presentation of consolidated financial statements in Ukraine is governed by both national and international standards. The main and positive changes are the implementation of its own classification for accounting and reporting. However, according to the results of the study, discrepancies in the classification of enterprises according to the laws «On Accounting and Financial Reporting in Ukraine», the Commercial Code of Ukraine and the Tax Code of Ukraine were educed. The criteria for the recognition of medium-sized enterprises by the economic code are not defined at all.It is worth noting that since the division of enterprises into large and small enterprises is often used in Ukrainian legislation, the simultaneous existence of several classifications can lead to disputed situations. Under the «updated» legislation, micro and small enterprises do not submit consolidated financial statements. However, medium and large enterprises consolidating financial data submit a new report «Consolidated Management Report».The globalization processes expected in Ukraine will lead to the unification of many enterprises and the requirement for consolidated reporting. It is necessary to expand the possibility of attracting foreign investment and loans, as well as access to foreign markets, ensuring greater trust from potential partners, etc
Keywords: business combinations, consolidated financial reporting, accounting, national standards, international standards.